3.55k likes | 3.79k Views
Discover the beauty and complexity of the Mandelbrot Set through fractal geometry and orbit calculations; learn to interpret the fate of orbits and fascinating mathematical patterns.
E N D
The Fractal Geometry of the Mandelbrot Set
The Fractal Geometry of the Mandelbrot Set How to count
The Fractal Geometry of the Mandelbrot Set How to count How to add
Many people know the pretty pictures...
but few know the even prettier mathematics.
Oh, that's nothing but the 3/4 bulb ....
...hanging off the period 16 M-set.....
...lying in the 1/7 antenna...
...attached to the 1/3 bulb...
...hanging off the 3/7 bulb...
...on the northwest side of the main cardioid.
Oh, that's nothing but the 3/4 bulb, hanging off the period 16 M-set, lying in the 1/7 antenna of the 1/3 bulb attached to the 3/7 bulb on the northwest side of the main cardioid.
Start with a function: 2 x + constant
Start with a function: 2 x + constant and a seed: x 0
Then iterate: 2 x = x + constant 1 0
Then iterate: 2 x = x + constant 1 0 2 x = x + constant 2 1
Then iterate: 2 x = x + constant 1 0 2 x = x + constant 2 1 2 x = x + constant 3 2
Then iterate: 2 x = x + constant 1 0 2 x = x + constant 2 1 2 x = x + constant 3 2 2 x = x + constant 4 3 etc.
Then iterate: 2 x = x + constant 1 0 2 x = x + constant 2 1 Orbit of x 2 0 x = x + constant 3 2 2 x = x + constant 4 3 etc. Goal: understand the fate of orbits.
2 Example: x + 1 Seed 0 x = 0 0 x = 1 x = 2 x = 3 x = 4 x = 5 x = 6
2 Example: x + 1 Seed 0 x = 0 0 x = 1 1 x = 2 x = 3 x = 4 x = 5 x = 6
2 Example: x + 1 Seed 0 x = 0 0 x = 1 1 x = 2 2 x = 3 x = 4 x = 5 x = 6
2 Example: x + 1 Seed 0 x = 0 0 x = 1 1 x = 2 2 x = 5 3 x = 4 x = 5 x = 6
2 Example: x + 1 Seed 0 x = 0 0 x = 1 1 x = 2 2 x = 5 3 x = 26 4 x = 5 x = 6
2 Example: x + 1 Seed 0 x = 0 0 x = 1 1 x = 2 2 x = 5 3 x = 26 4 x = big 5 x = 6
2 Example: x + 1 Seed 0 x = 0 0 x = 1 1 x = 2 2 “Orbit tends to infinity” x = 5 3 x = 26 4 x = big 5 x = BIGGER 6
2 Example: x + 0 Seed 0 x = 0 0 x = 1 x = 2 x = 3 x = 4 x = 5 x = 6
2 Example: x + 0 Seed 0 x = 0 0 x = 0 1 x = 2 x = 3 x = 4 x = 5 x = 6
2 Example: x + 0 Seed 0 x = 0 0 x = 0 1 x = 0 2 x = 3 x = 4 x = 5 x = 6
2 Example: x + 0 Seed 0 x = 0 0 x = 0 1 x = 0 2 x = 0 3 x = 4 x = 5 x = 6
2 Example: x + 0 Seed 0 x = 0 0 x = 0 1 x = 0 2 “A fixed point” x = 0 3 x = 0 4 x = 0 5 x = 0 6
2 Example: x - 1 Seed 0 x = 0 0 x = 1 x = 2 x = 3 x = 4 x = 5 x = 6
2 Example: x - 1 Seed 0 x = 0 0 x = -1 1 x = 2 x = 3 x = 4 x = 5 x = 6
2 Example: x - 1 Seed 0 x = 0 0 x = -1 1 x = 0 2 x = 3 x = 4 x = 5 x = 6
2 Example: x - 1 Seed 0 x = 0 0 x = -1 1 x = 0 2 x = -1 3 x = 4 x = 5 x = 6
2 Example: x - 1 Seed 0 x = 0 0 x = -1 1 x = 0 2 x = -1 “A two- cycle” 3 x = 0 4 x = -1 5 x = 0 6
2 Example: x - 1.1 Seed 0 x = 0 0 x = 1 x = 2 x = 3 x = 4 x = 5 x = 6